A comprehensive approach for assessing the economic contribution of forage and livestock improvement options to smallholder farming enterprises - Neil MacLeod; Scott Waldron; Shi-lin WEN (Journal of Integrative Agriculture, 2015)
The importance of livestock production activities to improving the livelihoods of smallholder farming households and the efficiency of their underlying farming systems is increasingly recognized. A rapid increase in livestock numbers, especially beef cattle, and special purpose forages is being promoted for smallholder farms which have traditionally undertaken subsistence cropping activities or simple livestock rearing activities using low quality feedstuffs. Because limited plantings of specialized forages combined with a poor knowledge of animal nutrition are a challenge to establishing sustainable livestock enterprises, much public policy and research is now being focused on the use of new forages and improved feeding practices. A number of economic studies have suggested that specialized forage growing and livestock feeding activities can make a positive contribution to smallholder welfare. The studies have typically compared the total level of farm or household income with and without livestock activities. Little attention is given to how much the new forage or livestock activities actually contribute to or draw resources from other farm activities to assess their real economic contribution to the enterprise, and the availability of simple tools to assist in making such assessments are limited. This paper describes a simple modelling approach that was developed for an Australian Centre for International Agricultural Research (ACIAR)-supported project to explore the real as opposed to apparent economic impact of integrating improved forages and livestock within smallholder farming systems in the Red Soils region of south-central China. Application of the model is demonstrated using a simple case study of a smallholder enterprise that plans to introduce a new beef cattle rearing activity to its existing farm activity mix. The case study highlights the importance of explicitly valuing transfers of resources between different farm activities to gauge the real contribution of those activities to economic returns.